2015
DOI: 10.1055/s-0035-1569482
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Nonoperative Treatment Demonstrates Success for Stiff Total Knee Arthroplasty after Failure of Conventional Therapy

Abstract: Astym therapy is a novel, nonoperative treatment that may be an effective treatment option for post-TKA patients suffering from persistent knee stiffness. Further studies are needed to validate this intervention as a part of cost-effective, standard treatment after TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…7,9 Astym therapy has been shown to be effective in improving ROM in patients with stiff knee/athrofibrosis following total knee arthroplasty. 14 Studies have demonstrated significant improvements in symptoms within a notably shorter duration with the use of Astym treatment compared to an eccentric program alone in treating hamstring and Achilles tendinopathies. 7,9,10 The results of this case demonstrate the positive treatment effects of Astym therapy in a young patient with cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 Astym therapy has been shown to be effective in improving ROM in patients with stiff knee/athrofibrosis following total knee arthroplasty. 14 Studies have demonstrated significant improvements in symptoms within a notably shorter duration with the use of Astym treatment compared to an eccentric program alone in treating hamstring and Achilles tendinopathies. 7,9,10 The results of this case demonstrate the positive treatment effects of Astym therapy in a young patient with cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,11 Achieving these treatment goals then reduces subjective complaints of restrictions in motion and improves function. 13,14 Astym therapy has consistently demon strated safety and effectiveness in the soft tissue conditions studied and is also well tolerated by patients. [7][8][9][10] However, it is important to recognize that instrumentassisted soft tissue mobilization (IASTM) interventions are not showing similar results.…”
Section: Introductionmentioning
confidence: 96%
“…3 Modern-day IASTM instruments vary in material (eg, stainless steel, plastic) and design 2 and are used to improve a variety of musculoskeletal conditions and associated outcomes. [4][5][6] As such, many IASTM instruments, companies, and proposed application protocols, including ASTYM (Performance Dynamics, Muncie, IN), 7 Fascial Abrasion Technique (FIT Institute, Niagara Falls, ON, Canada), 8 Graston Technique (Indianapolis, IN), 9 and HawkGrips (Conshohocken, PA), 10 to name a few, exist.…”
mentioning
confidence: 99%
“…The instrumentation is designed to assess the presence of dysfunctional tissue by amplifying the tactile sensation of the underlying texture of the soft tissues in order to provide the treating clinician with indications where rough or improperly organized tissue is located. Once an area of potential dysfunctional tissue is located, the clinician applies appropriate pressures and shear forces to that tissue to initiate a reparative cellular response in dysfunctional tissue (1,5,18,19). At the cellular level, Astym treatment has been shown to stimulate a regenerative response via stimulating the recruitment and activation of fibroblasts, which produce fibronectin, and thereby helps to facilitate soft tissue healing and remodeling (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%